The features of motivational-stimulating mechanism for labor activity in current Belarus - Nazarova, Darya V. (Journal of the Belarusian State University. Sociology, 2019)
The article covers the main elements of the structure of motivational-stimulating mechanism for labor activity: work conditions, the contract system of employment, just of remuneration and the specifics depending on the form of enterprise ownership. The factors influencing the motivational-stimulating mechanism of labor activity in todayʼs Belarus and identify their consequences have been found out.